A rapid lateral flow immunoassay strip for detection of SARS‐CoV‐2 antigen using latex microspheres. Issue 12 (6th November 2021) - Shen, Lin; Zhang, Qihan; Luo, Xiaolu; Xiao, Haolin; Gu, Miao; Cao, Liangli; Zhao, Feijun; Chen, Zhencheng
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) is a highly infectious and concealed virus that causes pneumonia, severe acute respiratory syndrome, and even death. Although the epidemic has been controlled since the development of vaccines and quarantine measures, many people are still infected, particularly in third‐world countries. Several methods have been developed for detection of SARS‐CoV‐2, but owing to its price and efficiency, the immune strip could be a better method for the third‐world countries. Methods: In this study, two antibodies were linked to latex microspheres, using 1‐(3‐dimethylaminopropyl)‐3‐ethylcarbodiimide hydrochloride and N‐hydroxysuccinimide, as the bridge to decrease the cost further and improve the detection performance. The specificity of the lateral flow immunoassay strip (LFIA) was tested by several common viruses and respiratory bacterial infections. Besides, the reproducibility and stability of the LFIAs were tested on the same batch of test strips. Under optimal conditions, the sensitivity of LFIA was determined by testing different dilutions of the positive specimens. Results: The proposed LFIAs were highly specific, and the limit of detection was as low as 25 ng/mL for SARS‐CoV‐2 antigens. The clinical applicability was evaluated with 659 samples (230 positive and 429 negative samples) by using both LFIA and rRT‐PCR. Youden's index (J) was used to assess the performance of these diagnostic tests. The sensitivity and specificity were 98.22% and 97.93%, respectively, and J is 0.9615. The sensitivity and specificity were 98.22% and 97.93%, respectively, and J is 0.9615. In addition, the consistency of our proposed LFIA was analyzed using Cohen's kappa coefficient (κ = 0.9620). Conclusion: We found disease stage, age, gender, and clinical manifestations have only a slight influence on the diagnosis. Therefore, the lateral flow immunoassay SARS‐CoV‐2 antigen test strip is suitable for point‐of‐care detection and provides a great application for SARS‐CoV‐2 epidemic control in the third‐world countries. Abstract : Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) is a highly infectious and concealed virus that causes pneumonia, severe acute respiratory syndrome, and even death. Although the epidemic has been controlled since the development of vaccines and quarantine measures, many people are still infected, particularly in third‐world countries. Several methods have been developed for detection of SARS‐CoV‐2, but owing to its price and efficiency, the immune strip could be a better method for the third‐world countries. However, some disadvantages of the strip can be fixed to decrease the cost and improve the performance. In this study, two antibodies were linked to latex microspheres, using 1‐(3‐dimethylaminopropyl)‐3‐ethylcarbodiimide hydrochloride and N‐hydroxysuccinimide, as the bridge to decrease the cost further and improve the detection performance. Unlike the reverse‐transcriptase‐polymerase chain reaction (rRT‐PCR) test, the results showed that the proposed strip had high specificity for SARS‐CoV‐2 antigen, and no cross‐reactions with other common viruses was observed. Most importantly, the detection limit was as low as 25 ng/ml, and the cost decreased to $0.15 per strip. Thus, the proposed SARS‐CoV‐2 antigen test strip offers a cheap, rapid, sensitive, specific, and visual method for SARS‐CoV‐2 antigen detection and shows great potential for COVID‐19 epidemic control in third‐world countries.